Forced Displacement, the Perpetuation of Autocratic Leadership, and Development in Origin Countries - Nicolás Cabra-Ruiz; Sandra V. Rozo; Maria Micaela Sviatschi (Institute of Labor Economics (IZA), 2025)
How does forced displacement shape development in origin countries? We examine the case of Venezuela, where nearly eight million people have been forcibly displaced. To do this, we compare municipalities with varying shares of foreign-born populations before and after international oil price shocks accelerated forced displacement between 2014 and 2019. Our findings show that municipalities with larger foreign-born populations in 1990, which also exhibited greater out-migration from Venezuela after 2014, experienced lower economic development and higher inequality. We highlight a new mechanism through which forced displacement facilitates the perpetuation of autocratic rule and hinders development: by weakening political opposition and enabling the growth of organized crime and illicit income sources. Using novel election data, we find that areas affected by mass forced displacement experienced lower voter turnout and opposition support, limiting political and social reforms. These areas also witnessed growth in organized crime and foreign non-state drug and human trafficking, which diminished incentives for economic change.
Keywords: O12; O15; O54; 330; forced displacement; electoral outcomes; economic growth; Venezuela